Fraksi Radiasi Matahari pada Sistem Agroforestri Cempaka Solar Radiation Fraction in the Cempaka Agroforestry System - Randi Purba; Semuel P. Ratag; Josephus I. Kalangi (COCOS, 2018)
ABSTRACT Â Plant growth and development depends on internal factors (genetic) and external factors (environment). Solar radiation (external factor) is an energy source needed in plant growth. In agroforestry systems the existence of woody species (trees) will reduce the level of light received by agricultural crops (annual crops). The purpose of this study was to determine the fraction of solar radiation in the Cempaka agroforestry system. The research was conducted in three locations, namely Lemoh Barat Village (295 masl), Rumoong Atas Village (489 masl) and Kinilow Satu Village (652 masl). Direct measurement of radiation using a solarimeter device placed in 3 observation points at each location, while the measurement of radiation fraction estimation was taken data of tree canopy width, tree height, tree spacing width and land area. The results of direct measurements of radiation obtained at the Lemoh Barat Village agroforestry area were 62%. Rumoong Atas Village were 51% and Kinilow Satu Village were 53%. The estimation results obtained by Lemoh Barat Village were 74%, Rumoong Atas Village were 62% and Kinilow Satu Village were 26%. Key words: Radiation Fraction, Agroforestry, Cempaka